PENGARUH KESEMPATAN INVESTASI, LEVERAGE, DAN LIKUIDITAS PADA KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Mawarni, Luh Fajarini Indah; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
Dividend policy is the deciision of the profit will be distribute to shareholders as dividends or as investment financing in the future . The percentage of earnings paid to shareholders as dividends cas namely Parliament ( Dividend Payout Ratio ) . This  study was conducte to  examine the effectt of the variable  investment opportunity , Leverage , and Liquidity On Dividend Policy Manufacturing Company listed on the Stock Exchange Period 2010-2012. Total population in this study of 391 companies , with purposive sampling of data obtained as much as 72 observations . The results show Leverage Investment Opportunity and negative effect on dividend policy and liquidity has a positive effect on Dividend Policy . Adjusted R Square of 0.294 . This means that 29.4% of the variation Dividend policy is influenced by the variation of the variable investment opportunities , leverage , and liquidity , while the remaining 70.6 % influenced by other factors outside the model .
Keywords: dividend policy , investment opportunities , leverage , and liquidity